(untitled) (Baghdad Science Journal, 2023)
The researchers wanted to make a new azo imidazole as a follow-up to their previous work. The ligand 4-[(2-Amino-4-phenylazo)-methyl]-cyclohexane carboxylic acid as a derivative of trans-4-(aminomethyl) cyclohexane carboxylic acid diazonium salt, and synthesis a series of its chelate complexes with metalions, characterized these compounds using a variety technique, including elemental analysis, FTIR, LC-Mass, 1H-NMRand UV-Vis spectral process as well TGA, conductivity and magnetic quantifications. Analytical data showed that the Co (II) complex out to 1:1 metal-ligand ratio with square planner and tetrahedral geometry, respectively while 1:2 metal-ligand ratio in the Cu(II), Cr(III), Mn(II), Zn(II), Ru(III)and Rh(III)complexes with octahedral geometry except Mn complex has tetrahedral geometry. The Ligand functions as a neutral tridentate ligand in all complex investigations, coordinating Cr(III), Zn(II), Ru(III), and Rh(III) ions via the N atom of amine and azo groups, as well as the O phenolic OH group. When coordinated with the Cu(II), Co(II), and Mn(II) ions via the two N atoms of the amine and azo groups, this Ligand functions as a neutral bidentate.